Peramalan Jumlah Penumpang di Bandar Udara Soekarno-Hatta dengan menggunakan Pemulusan Eksponensial Tripel tipe Holt-Winter dan tipe Brown - Rahmah Aziz; Helma Helma (UNIVERSITAS NEGERI PADANG, 2022)
The main airports in Indonesia, including at Soekarno-Hatta, are deserted, due to government policies to overcome the Covid-19 disease outbreak. The number of passengers has fallen drastically, every month the plane is erratic in carrying passengers. With a pandemic like this, the airline must make a strategy to avoid losses. To overcome this problem, the purpose of this study is to predict the number of passengers at Soekarno-Hatta Airport during the pandemic using triple exponential smoothing of Brown type and Holt-Winter type. In the triple exponential smoothing method, trend analysis is carried out and followed by smoothing three times.